Analisis SWOT dan Strategi Agresif Pengembangan Wisata Pemandian Alam Uluna Kabupaten Minahasa - Feisel Kristopel Rompas; Xaverius Erick Lobja; Irfan Rifani (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
This research aims to identify internal and external factors that support the development of tourist attractions as well as strategies that need to be implemented in developing the Uluna natural baths tourist attraction. The analysis technique uses SWOT with a qualitative descriptive approach. The research results show that based on IFAS (0.5) and EFAS (1.80), the position of Uluna Natural Baths is in quadrant I, meaning it has advantages with the power to take advantage of development opportunities. The strategy implemented is an aggressive growth strategy (growth-oriented strategy). The recommended strategy is Strength-Opportunities (S-O). The strategies that need to be implemented are improving the quality of infrastructure to support tourism development, maximizing the management of existing tourism potential, optimizing community participation and awareness in preserving and introducing tourist objects and natural products, improving the performance of tourism managers by completing socio-economic facilities to support community activities in carrying out tourism activities, as well as making government regulations regarding the management of the Uluna natural baths as a tourist attraction.